Distribution Conventionality in the Movie Sector: An Econometric Analysis of Cinema Supply - Alan Collins; Antonello E. Scorcu; R. Zanola (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
This paper empirically analyzes the impact of several factors on a 'conventionality index' in the specific context of the cinema exhibition sector. To our knowledge, it is the first time that a standard conventionality index has been constructed for this purpose. Econometric analysis of the determinants of variation in this index provides decision-makers with an empirical focus for analyzing distributional aspects of the movie exhibition market, with particular emphasis on product differentiation. Specifically, (i) do cinemas based in a city area have a different or 'specialized' focus in contrast to cinemas in small towns? Or, (ii) do multiplexes have a different or more specialized focus in comparison with cinemas? To this end, cross-sectional econometric models are estimated to help analyze these effects in three Italian regions for a sample of cinemas covering the 2006 season.
Keywords: 330